Analisis Waktu Pendistribusian Bahan Baku Utama Produksi Pupuk NPK di PT. Pupuk Kujang - Sri Mulyati; Akhsani Nur Amalia (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
PT. Pupuk Kujang currently does not have a standard time in the distribution of NPK fertilizer raw materials, especially for urea, KCL, and DAP, so that there are often delays in the arrival of raw materials which causes delays in the production process. The purpose of this research is to find out the standard time  needed in the distribution of NPK raw materials, namely urea, KCL, and DAP so that there is no delay in the raw materials that can reach the transit warehouse. Observations were carried out directly by researchers in the NPK 2 factory area by observing and interviewing field supervisors. The results obtained from the data processing that have been calculated obtained the standard time (standard time) using the time study method with each urea distribution of 1971,42 seconds , KCL of 861,17seconds, and DAP of 856,66 seconds. The time includes starting from loading raw materials, traveling raw materials to scales, weighing raw materials, traveling raw materials to transit warehouses, and unloading raw materials in transit warehouses. Keywords: Distribution, Standard Time, Time Study